Combined effects of maternal supplementation of iron, calcium, folic acid, and multivitamin during pregnancy on obesity in Chinese preschoolers born macrosomia - Yan, Ming-Fei; Strodl, Esben; Yang, Wei-Kang; Yin, Xiao-Na; Wen, Guo-Min; Sun, Deng-Li; Xian, Dan-Xia; Zhao, Ya-Fen; Chen, Wei-Qing (Frontiers in Pediatrics, 2025)
ObjectiveChildhood obesity has become a global public health crisis. Previous studies have shown that nutritional supplementation during pregnancy may be protective against offspring obesity. However, the research in this area is still emerging and the impact of moderators, such as birth weight, upon outcomes has not been fully explored. This study aimed to examine the combined effect of maternal supplementation with iron, calcium, folic acid, and multivitamin during pregnancy on the risk of obesity in Chinese preschoolers born macrosomia.MethodsA total of 6,031 singleton children, born macrosomia, aged 3–6.5 years old were recruited from Longhua District in Shenzhen of China in 2021. Their mothers were asked to complete a structured questionnaire for collecting the sociodemographic characteristics of the child and parents, the child's birth-related characteristics, and maternal supplementation with iron, calcium, folic acid, and multivitamins during pregnancy. The children's weight and height were measured using a standardized method by well-trained medical staff from the Women's and Children's Hospital of Longhua District of Shenzhen.ResultsAfter controlling for confounding variables, including other nutrients, the results of a series of logistic regressions showed that only iron supplementation (AOR = 0.75, 95% CI = 0.60–0.92) during pregnancy was negatively associated with the presence of obesity in preschoolers born macrosomia in boys. In contrast, there was no independent associations between maternal prenatal ingestion of iron, calcium, folic acid, or multivitamin supplements and obesity in preschool girls born macrosomia. Examination of interaction effects through crossover analyses showed that maternal supplementation with both iron and calcium (AOR = 0.68, 95% CI = 0.49–0.94), and both iron and multivitamins (AOR = 0.64, 95% CI = 0.48–0.86) during pregnancy significantly reduced the risk of obesity in male preschoolers born macrosomia. Furthermore, interaction analysis found a multiplicative interaction between maternal iron and multivitamin supplementation during pregnancy on the risk of obesity in male preschoolers born macrosomia (IOR = 0.52, 95% CI = 0.35–0.79).ConclusionOur findings suggest that iron supplementation during pregnancy may reduce the risk of obesity in preschoolers born macrosomia in boys, with this effect enhanced with the combined ingestion of calcium and multivitamin supplementation.